1969
DOI: 10.1172/jci106098
|View full text |Cite
|
Sign up to set email alerts
|

Studies of arteriosclerosis in japanese and american men

Abstract: A B S T R A C T The proportions of fatty acids in lipids of subcutaneous adipose tissue was compared in closely age-matched, urban men from two populations with a great difference in mortality from arteriosclerosis, namely in 50 Americans and 56 Japanese aged 15-65 yr who had died suddenly and unexpectedly. Specimens from both groups were analyzed side by side for fatty acids by gas-liquid chromatography. Compared with Japanese, Americans had significantly (P < 0.01) higher proportions of lauric (+ 0.2%), myri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

1977
1977
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…The adipose tissue profile shown in Fig. 41.2 is similar but not identical to those described in other countries and populations, such as Americans or Japanese [15], thus providing evidence for the greater influence of dietary contribution over endogenous metabolism on the fatty acid composition of adipose tissue.…”
Section: Fatty Acid Composition Of Adipose Tissuementioning
confidence: 63%
See 2 more Smart Citations
“…The adipose tissue profile shown in Fig. 41.2 is similar but not identical to those described in other countries and populations, such as Americans or Japanese [15], thus providing evidence for the greater influence of dietary contribution over endogenous metabolism on the fatty acid composition of adipose tissue.…”
Section: Fatty Acid Composition Of Adipose Tissuementioning
confidence: 63%
“…These populations are well known for the high consumption of olive oil in their diets [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28]. In other populations, it has been demonstrated that the consumption of coconut oil increases the adipose tissue content of lauric and myristic acids, both SFAs [29], and adipose tissue samples from Japanese populations presented elevated proportions of PUFAs of the n-3 family such as eicosapentaenoic (EPA; C20:5n-3) and docosahexaenoic (DHA; C22:6n-3) acids, which were associated with high fish intake [15]. When vegetarians and nonvegetarians were compared, the former had higher proportions of linoleic acid in their adipose tissues, and were also believed to have higher PUFA intakes [30].…”
Section: Types Of Diet and Adipose Tissue Compositionmentioning
confidence: 99%
See 1 more Smart Citation
“…The common point of those FAs source is their exogenous source, which confirmed us that TG + PL variables in IC 4 can reflect the exogenous FAs. To specify the sources of exogenous FAs, we calculated the correlation coefficients between loading values of TG + PL variables and reported adipose FA composition for Japanese, which is low ( ) 30 . Therefore, we refused the assumption that IC 4 reflects the adipose composition but accepted the suppose that IC 4 represents exogenous FAs.…”
Section: Resultsmentioning
confidence: 99%
“…Some previous publications noted that saturated and unsaturated fats can have a different impact on metabolism 9 and are potentially related to cardiac disorders. 10 , 11 , 12 Thus, noninvasive assessments of fat composition by MRS could also become a powerful tool in relevant research. In tissues where lipid concentrations are very high, such as in bone marrow, fat compositional analysis by 1 H MRS can be powerful.…”
Section: H Mrsmentioning
confidence: 99%